Indications and prognostic outcome of inferior vena cava filter: Almoosa Hospital’s experience - Safwat A.M. Eldaboosy; Mahmoud Farouk; Abdullah Farouk; Ahmad Antar; Amgad Awad; Mohamed O Nour; Gasmelseed Y Ahmed (Egyptian Journal of Chest Disease and Tuberculosis, 2022)
Background An inferior vena cava (IVC) filter is useful in patients with venous thromboembolism (VTE) who have any of the following conditions: contraindications to anticoagulants, recurrent pulmonary embolism (PE) despite anticoagulants or complications related to anticoagulants, and low cardiopulmonary reserve. This study aimed to assess indications, efficacy, and outcome of IVC filter insertion for patients with VTE. Patients and methods A retrospective study was conducted at Almoosa Hospital, Al Alhsa, Kingdom of Saudi Arabia, in the period between August 2017 and September 2020. All adult patients who underwent IVC filter were included. Results The study included 1350 cases. The patients were divided into two groups: group 1 included 1310 patients who had VTE without the need for an IVC filter, and group 2 included 40 patients, 39 of whom had VTE and required an IVC filter, and one patient with polytrauma (cerebral hemorrhage, pelvic hematoma) in whom an IVC filter was used prophylactically. A total of 40 IVC filters were used. Thirty (75%) patients had submassive PE with pulmonary hypertension and low pulmonary vascular reserve, nine (22.5%) patients had VTE with contraindications for an anticoagulant (due to gastrointestinal bleeding, cerebral hemorrhage, or major trauma), while one (2.5%) patient had an IVC filter inserted prophylactically although no VTE was present. The rate of IVC removal was 30% (12 cases), with no reported complications of IVC insertion or removal, except in one case where the filter was removed in two separate sessions. Conclusion IVC filter insertion, when used correctly, is a safe and effective method of preventing a potentially fatal PE by blocking the passage of thrombi from the lower extremities and pelvis to the lungs when used correctly.